2020
DOI: 10.1111/nbu.12462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating current egg consumption patterns: Associations with diet quality, nutrition and health status in the UK National Diet and Nutrition Survey

Abstract: Dietary habits are constantly evolving with changes in culture, economics and the food supply. In the UK, red meat intakes have been declining for more than a decade, while egg consumption has increased in tandem with interest in healthy, sustainable diets. To explore current dietary habits of egg consumers and non‐consumers and potential implications for nutrition and health, we analysed dietary records from 647 adults participating in Year 9 (2017) of the UK National Diet and Nutrition Survey (NDNS). Mean co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…This shows that when overt deficiency is concerned, a decrease in energy is more important than the source of protein in the diet. In more detail, we found that animal protein intake from eggs has a more salient beneficial weight on deficiency risk, which may be due to the high contribution of its protein package to iodine, riboflavin, retinol, and B12 intakes (63,64). It also suggests that this protein source should be given a preference over other animal protein sources when shifting toward a diet with fewer animal products.…”
Section: Discussionmentioning
confidence: 87%
“…This shows that when overt deficiency is concerned, a decrease in energy is more important than the source of protein in the diet. In more detail, we found that animal protein intake from eggs has a more salient beneficial weight on deficiency risk, which may be due to the high contribution of its protein package to iodine, riboflavin, retinol, and B12 intakes (63,64). It also suggests that this protein source should be given a preference over other animal protein sources when shifting toward a diet with fewer animal products.…”
Section: Discussionmentioning
confidence: 87%
“…Yumurta sağlıklı ve dengeli beslenmenin bir parçası olarak kabul edilmektedir [105]. Vega-Lopéz ve arkadaşları [106] tarafından yapılan bir çalışmada, yumurta tüketen ve tüketmeyen bireylerin diyet kaliteleri arasında anlamlı bir fark olmadığı bulunmuştur (p>0,05).…”
Section: Diyet Kalite İndeksi-international (Dqi-i)unclassified
“…Meşrubat tüketimi ile BKİ arasındaki ilişkiyi daha net ortaya koyan araştırmaların yapılması gerekmektedir. [105] tarafından yapılan bir araştırmada, yumurta tüketen kadınların BKİ değerlerinin, tüketmeyenlere göre daha yüksek oranda normal sınırlar içinde olduğu gösterilmiştir (p<0,05). Vega-Lopéz ve arkadaşları [106] yapmış oldukları araştırmada, yumurta tüketen (29,9±3,7 kg/m 2 ) ve tüketmeyen (29,3±3,3 kg/m 2 ) bireylerin BKİ değer ortalamaları arasında anlamlı bir fark saptamamışlardır (p<0,05).…”
Section: Beden Kütle İndeksi (Bki̇)unclassified
“…If we consider more recent data from mainly adult dietary intakes, the UK National Diet and Nutrition Survey has shown an increase in egg consumption of 23% between 2008–2009 and 2016–2017 19 . Additionally, consumer purchase of eggs increased by 49% between 2008 and 2019 20 . If adults have increased their intake of eggs, has this also resulted in a change in confidence in offering them to infants?…”
Section: Introductionmentioning
confidence: 99%
“…19 Additionally, consumer purchase of eggs increased by 49% between 2008 and 2019. 20 If adults have increased their intake of eggs, has this also resulted in a change in confidence in offering them to infants?…”
Section: Introductionmentioning
confidence: 99%